Digest of the Laws of the State of Ala. 391-92 (1833), sec. 7 - (:unkn) unknown (General Publisher, 1833)
Prohibited any “slave” from keeping or carrying any gun or ammunition without permission from a justice of the peace.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES